A secure mobile communication approach based on information hiding. (13th February 2007) - Chen, Yun-Feng; Li, Tao; Gao, Dong-Ni; Hu, Xiao-Qin; Zhang, Xiao-Ping; Liu, Jin
A secure mobile communication approach is proposed in this paper. The security of our approach is guaranteed by certification authority and information hiding technique. During the communication, the identity of users will be validated first. The secure speech will be transferred hidden in the public speech. When the public speech arrives at the receiving side, the secure speech will be restored. This approach solves the problem of wiretapping attack, voice-imitating attack and denials after communicating during communication. The experimental results show that this approach is a good solution to mobile secure communication.